السياسة التربوية في الجزائر دراسة تقويمية لواقع الإصلاحات في الطورين الأول والثاني للفترة الممتدة : من سنة 2000 إلى 2018 - ترممو, محمد (جامعة الوادي University of Eloued, 2018)
"يعتبر التعليم عنصرا أساسيا للتن مية , فهو يساعد على تمكين الناس من إكتساب قدرات فكرية وعلمية ذات مستوى راقي , فأغلب دول العالم اليوم متقدمة كانت أو نامية تعطي إهتماما كبيرا لنظامها التربوي وكلها عزم على مواكبة الركب الحضاري الذي لا يأتي اليوم إلا من خلال سياسية تربوية وتعليمية قائمة على أسس عالمية وبالتالي كانت عملية إصلاح هذه النظم مطلبا مُهمًا خاصة على المستويين الأول والثاني . وبالنسبة للجزائر فقد شهد التعليم بمختلف مستوياته جملة من الإصلاحات والتحويرات منذ الإستقلال إلى سنة 2018, تسعى من خلالها السياسة التربوية الجزائرية إلى محاولة تفعيل دور التعليم في مجال بناء الوطن بعد مرحلة التحولات التي عرفتها الجزائر، على مختلف الأصعدة السياسية والاجتماعية والاقتصادية. هذا الإصلاح بدوره وضع الجزائر أمام تحديات كبيرة داخلية وخارجية حيث تتمثل تلك التحديات الداخلية في تركيز المدرسة على التعليم والتنشئة الاجتماعية و التأهيل وكما هي مرتبطة بالعصرنة وإستكمال ديمقراطية التعليم وبلوغ النوعية لفائدة أكبر عدد من التلاميذ , ثم التحكم في العلوم والتكنولوجيا , أما التحديات الخارجية فتتمثل في عولمة الإقتصاد مما يترتب عليه من متطلبات تأهيل بمستوى عالي أكثر فأكثر في مجتمع الإعلام والاتصال وفي التطور العلمي والتقني الذي يساعد على بروز شكل جديد للمجتمع أي مجتمع المعرفة والتكنولوجيا. " "Education is an essential element of development. It helps to enable people to acquire intellectual and scientific capabilities of a high level. Most of the countries of the world today are developed or developing, giving great attention to their educational system, all of which are determined to keep up with the cultural grassroots that today comes only through an educational and educational policy On a global basis and therefore the process of reform of these systems was an important demand, especially at the first and second levels. For Algeria, education at various levels has undergone a number of reforms and adjustments since then Istiqlal to 2018, through which the Algerian educational policy to try to activate the role of education in the field of nation building after the stage of transformations experienced by Algeria, at various levels of political, social and economic. This reform, in turn, put Algeria in the face of major internal and external challenges. These internal challenges are the school's focus on education, socialization and rehabilitation, as it is related to modernization, completion of education democracy, quality attainment for the largest number of students, and control of science and technology. The globalization of the economy, which entails the requirements of higher and higher qualification in the information and communication society and in the scientific and technical development, which helps to emerge a new form of society, ie the society of knowledge and technology. "
سياسة عامة وإدارة محلية
Keywords: النظام التربوي، المقاربة بالكفاءة، إصلاح التعليم، تنظيم التعليم.; Educational system, Competency approach, Education reform, Organization of education.